The Level of Compliance with AAOIFI Standards by Islamic Banks in UAE - Ambashe, Mohamud (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
The unprecedented growth in Islamic financial products and services and the emerging orientation that the conventional International Financial Reporting Standards (IFRS) are incompatible with Islamic beliefs and values. This led to the establishment of the Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI). However, the actual practice and level of compliance with the AAOIFI standards among Islamic banks in the United Arab Emirates (UAE) are entirely unknown hitherto. Therefore, this study aims to measure the extent of compliance with AAOIFI standards by Islamic banks in the UAE. Via the extensive review of academic publications and document analysis of overarching AAOIFI standards, disclosure items were established and categorized into four: general corporate information, primary statements, accounting policies statements, and notes to the accounts. The 2018 financial statements of 7 Islamic banks in the UAE were evaluated to assess their level of compliance with the AAOIFI disclosure items using the unweighted disclosure index. The findings indicate that the level of compliance with AAOIFI on general corporate information was very high in all Islamic banks investigated, while the primary statements, accounting policies statements, and notes to the accounts recorded a low level of disclosure. This study contributes to the existing body of knowledge on the aspect of AAOIFI compliance among Islamic financial institutions, especially in the UAE, and enlightens the Islamic financial institutions on the areas of AAOIFI that need to be adequately adopted.